Congenital Midline Nasal Anomalies. Issue 4 (1st October 2017) - Vora, Niraj; Kalagiri, Ram; Guillory, Bryan; Shetty, Ashita; Raju, Venkata Nakta; Powitzky, R. K.; Beeram, Madhava R.
Abstract : Congenital midline nasal anomalies are rare, with a prevalence of 1 in 20, 000 to 40, 000 births and with 5% to 7% of them being nasal glioma. Differential diagnoses of nasal anomalies include nasal dermoid cysts, gliomas, encephaloceles, nasal polyps, and some other rare anomalies. Due to current medical technological advancements, most of these anomalies are easily correctable, though delaying management may lead to fatal effects. This report describes two cases–one of nasal glioma and one of nevus lipomatosus cutaneous superficialis–that presented as respiratory distress in a newborn. Approximately 10 to 20 cases of these two conditions have been described; notably, this is the second documented case of nevus lipomatosus cutaneous superficialis with nasal presentation.